2003
DOI: 10.1162/00335530360535144
|View full text |Cite
|
Sign up to set email alerts
|

Does Market Experience Eliminate Market Anomalies?

Abstract: This study examines individual behavior in two well-functioning marketplaces to investigate whether market experience eliminates the endowment effect. Field evidence from both markets suggests that individual behavior converges to the neoclassical prediction as market experience increases. In an experimental test of whether these observations are due to treatment (market experience) or selection (e.g., static preferences), I nd that market experience plays a signi cant role in eliminating the endowment effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
572
6
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,012 publications
(667 citation statements)
references
References 17 publications
62
572
6
5
Order By: Relevance
“…The sunk cost fallacy is generally related to the endowment effect in the sense that the amount that the buyer has sunk can be viewed as an endowment (Genesove and Mayer 2001). Endowment effects are less intense among more experienced persons (List 2003(List , 2004. Identifying more experienced buyers as those who buy more expensive cars or live in more expensive homes, we find mixed evidence on the proposition that more experienced buyers are less influenced by sunk costs.…”
Section: Ustomers Who Had Initially Paid More For a Season Subscripmentioning
confidence: 71%
“…The sunk cost fallacy is generally related to the endowment effect in the sense that the amount that the buyer has sunk can be viewed as an endowment (Genesove and Mayer 2001). Endowment effects are less intense among more experienced persons (List 2003(List , 2004. Identifying more experienced buyers as those who buy more expensive cars or live in more expensive homes, we find mixed evidence on the proposition that more experienced buyers are less influenced by sunk costs.…”
Section: Ustomers Who Had Initially Paid More For a Season Subscripmentioning
confidence: 71%
“…It appears that loss aversion, but not the status quo bias phenomenon, provides sound behavioral foundations for the endowment effect. In particular, the finding that the endowment effect disappears in environments with repeated trades -see, for instance, List (2003List ( , 2004) -entails the same for loss aversion but not for status quo bias.…”
Section: Loss Aversion Versus Status Quo Biasmentioning
confidence: 99%
“…Experts, those with high levels of experience in a specific domain, are less susceptible to some cognitive and affective errors than are novices. For example, in collectables markets, List (2003) found that market experience mitigated the endowment effect. Experienced traders were less prone to the endowment effect than were less-experienced traders.…”
Section: Experience and Behavior 10mentioning
confidence: 99%